Modelagem computacional de transientes hidráulicos em ventosas de tríplice função e non slam considerando as curvas de admissão e expulsão de ar - Barbosa, João Marcelo Costa (2015)
sucker triple function acts on admission and / or expulsion of air in the pipe, protecting piping and equipment against the effects of air and accumulation water hammer. Through kinetic hole, she admits lot of air when the pressure inside the pipe becomes lower than atmospheric, and expels air after separation column at a superatmospheric pressure. The inlet region air, the suction orifice "Non slam" admits large volume of air through the orifice Kinetic and starts expelling air through the same hole. From a certain Positive pressure value, the kinetic orifice is closed and opens a lower orifice diameter hole called "Non slam", cushioning, thus, the shock of columns they were separated liquid. In this paper, we propose a methodology for calculating the admission rates and expulsion of air in transient from the curves provided by the manufacturers. The work aims to minimize the lack of information Experimental suction cups on the basis of the curves for the determination of makers the admission rates and expulsion of air. In this study we compared the effect of using a single air discharge coefficient for input and another for output only Air versus consider the variation of these coefficients discharge pressures as range. The UFC7 computer program written in Java, implements the transient Hydraulic with its boundary conditions